Children's conversation management : native speaker - non-native speaker talk - Hirvonen, Tuula (1996)
The present study explores 8-10-year-old children's peer talk in free play activities. The subjects are ten native English-speaking children and eight learners of English. Studies on foreigner talk have established modification s that are generally observed by adults when talking to speakers a t low proficiency levels. Conversations with peers are an important learning context for child second language learners. The native speakers' ability and willingness to modify when speaking to a learner may have important repercussions for the learner's opportunities to take part in conversations. The present study aims to explore individual variation between children talking with non-native speaking peers: context-dependent (register) variation and speaker-dependent (individual style) variation in addition to variation according to the learner's proficiency level. The data were collected in conversation dyads in free play sessions, both native speaker-learner and native speaker-native speaker interactions. The data were analysed at four different levels: interactional, sequence, exchange and functional. The interactional space, the ways in which the task and communication breakdown are negotiated, and the support given to the learners in conversation were explored using nearly thirty variables at the four levels. The results showed individual variation between native speakers in how they initiated topics, responded to learner initiations and used strategies for avoiding conversational problems, and hence in how they allowed space for the learner to take part in the conversation. Moreover, the native speakers approached meaning negotiations differently: some children were more inclined to concentrate on the task, whereas others were interpersonally oriented, negotiating about the learner's topics and providing support. There were also indications of context-dependent strategic choices and speaker-dependent features in the use of initiations and some strategies. The study shows the subjects to have acquired individual approaches to the foreigner register, to exhibit differences in willingness to modify and to take the learner into account, and to be able to modify according to the learner's proficiency level.